Error analysis in prescriptions dispensed in a Basic Health Unit (Research, Society and Development, 2020)
The study aims to evaluate the conformity of the prescriptions dispensed in a Basic Health Unit, according to RDC nº 357/2001. This was a cross-sectional, observational and retrospective study carried out from January to December 2017 at the Pharmacy of the Basic Health Unit of Vila Coelho Dias in Bacabal - Maranhão, using as sample the second copies of medical prescriptions that were retained in the pharmacy. During the analyzed period, 922 prescriptions were found; of these, 488 (52.9%) were excluded because they were considered transcriptions made by nurses. Of the total medical prescriptions analyzed, 42 (10%) were illegible, 96 (22%) legible and 296 (68%) poorly legible. The study also shows that 100% of the prescriptions have the patient's name, but age and address are absent in all prescriptions. Regarding the variables related to the prescription, 100% presented the date and signature of the prescriber and only 18 (4.15%) presented erasures. Note that 67.1% (n=291) reported dosage, concentration was absent in 34.4% (n=144), pharmaceutical form was present in 67.2% (n=292), duration of treatment was absent in 85.71% (n=372) and 49.1% (n=231) had the route of administration. It was found in the present study that prescription errors ranged from readability to the variables analyzed, both for the patient, prescriber and the drug, which allowed us to conclude that the legal aspects of the prescription continue to be violated by prescribers.